Circulating makorin ring finger protein 3 levels decline in boys before the clinical onset of puberty. Issue 6 (June 2016) - Varimo, Tero; Dunkel, Leo; Vaaralahti, Kirsi; Miettinen, Päivi J; Hero, Matti; Raivio, Taneli
Abstract : Objective: Makorin ring finger protein 3 ( MKRN3 ) gene restrains the hypothalamic–pituitary–gonadal axis. In girls, peripheral levels of MKRN3 decline prior to the onset of puberty. We described longitudinal changes in serum MKRN3 levels in boys before and during puberty and assessed the effect of inhibition of estrogen biosynthesis on MKRN3 levels. Design: Longitudinal serum samples from a double-blind, randomized controlled study in 30 boys (age range: 9.1–14.2years) with idiopathic short stature who received placebo (Pl; n= 14) or aromatase inhibitor letrozole (Lz; 2.5mg/day; n= 16) for 2years. Methods: We analyzed the relationships between serum MKRN3 and clinical and biochemical markers of puberty by using summary measures. Results: Serum MKRN3 declined by 669±713 pg/mL per year ( P <0.001). This change was biphasic, as the levels decreased during Tanner genital stage G1 (–2931±2750 pg/mL per year) and plateaued thereafter (–560±1510 pg/mL per year) ( P< 0.05). During G1, MKRN3 levels in Lz-treated subjects decreased slower than in Pl-treated boys (–782±3190 vs –2030±821 pg/mL per year, P< 0.05). The decrease in serum MKRN3 levels in G1 was associated with increases in LH ( r= –0.5, P< 0.01), testosterone ( r= –0.6, P< 0.01), and inhibin B ( r= –0.44, P< 0.05) ( n= 26). Conclusion: Peripheral MKRN3 levels in boys appear to serve as a readout of the diminishing central inhibition that controls the onset of puberty.